Mesoporous ordered films via self-assembly: trends and perspectives - Innocenzi, Plinio (Chemical science (Cambridge), 2022)
The synthesis of ordered mesoporous films via self-assembly represents one of the main accomplishments in nanoscience. In fact, controlling the complex chemical–physical phenomena that govern the process triggered by the solvent's fast evaporation during film deposition has represented a challenging task. Several years after the first articles on the subject, the research in the field entered a new stage. New advanced applications based on the peculiar properties of mesoporous films are envisaged while basic research is still going on, especially to clarify the mechanism behind self-organization in a spatially defined environment and the physics and chemistry in mesoscale porosity. This review has been dedicated to analysing the main trends in the fields and the perspective for future developments.